The multifaceted impacts and reasons of the Ukraine war: a theoretical analysis - Tokatli, Seda Gözde (Penerbit Universiti Kebangsaan Malaysia, 2024)
The armed conflict between Russia and Ukraine that began in 2022 has reached diverse effects and reasons in the system. But Russia deems Ukraine within her sphere of influence and has been infuriated at Ukraine’s nearness with the West and her desire to join NATO or the EU. The main purpose of this article is to discuss the multiple effects of the conflict on the global powers and explain how states’ national interests and goals have driven their responses in the foreign policy. The main driving point of this article is to focus on the several reasons and effects of Ukraine war that shakes the balance between the global powers in the world and how it disturbs the already existing order. This article will benefit from the perspectives of realism theory when deciphering the causes of the conflict between Russia and Ukraine and the regional and global implications of this conflict in various ways. To reveal the increasing power race within the system, to be able to see the changing balances within the framework of the concept of national interest and to see the impact of the war within the system, the theory of neorealism has been included in the study. This article will focus on three levels of analysis such as individual, state, and systemic in examining the main driving forces behind of Russia and Ukraine conflict. This war was not only occurred between Russia and Ukraine, it has had also created a huge impact on the other regions or international organizations in a different area. Regardless of the outcome of the war in Ukraine, Russia remains the most dangerous, immediate, and long-term threat to the Euro-Atlantic community and rules-based world order. During this study, it will focus on the descriptive theory by using comparison methods and techniques.